(untitled) (Acta Scientiarum. Biological Sciences, 2012)
This study aimed to evaluate the effect of nutrient depletion during the cultivation of the microalgae Tetraselmis tetrathele, and to verify the algal growth and productivity in different culture media (Guillard f/2 and Conway). The experiment was conducted in nine-liter containers, with working volume of eight liters, salinity 35 ± 2â€°, temperature 28 ± 1°C, with constant light and aeration, around 200 Î¼E cm-2 s-1 and 3 L air min.-1. Results showed that microalgae development caused nutrient depletion, since we observed an inversely proportional relationship between nitrate concentration and algal biomass during the cultivation. Regarding the culture media, a higher algal productivity was observed in the cultivation developed in Conway medium (p < 0.05), obtaining at the end of the cultivation, biomass of 3.38 ± 0.02 g L-1. In the Guillard medium, only 2.47 ± 0.05 g L-1 was obtained. The cultivation in Conway medium presented better results concerning microalgae growth, with a more pronounced exponential phase. This was due to the higher nitrate availability, which was reduced more rapidly in the culture medium Guillard f/2.